Scaling up the use of low-emissions development (LED) research outputs in Kenya: Operationalizing climate-smart agriculture strategy in the local action plan - Khatri-Chhetri, Arun; Odhong’, Charles; Lamanna, Christine; Kamau, Hannah N.; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Key messages – The climate-smart agriculture (CSA) Data Atlas and Training Guidebook can help operationalize Kenya’s Climate-Smart Agriculture Strategy (KCSAS) and its framework at the county level by building capacity of local CSA stakeholders and designing the county CSA plans. – The updated nationally determined contribution (NDC) of Kenya recognizes capacity building need for scaling the process of CSA county plan design and implementation in Kenya. This can lead to increased investment from the public and private sectors, uptake of CSA options, and can generate substantial adaptation and mitigation gains in Kenya’s agriculture sector. – Advancing the impact pathway for large-scale adaptation and mitigation impact of CSA plans requires strong collaboration among the national and county governments, development of self- financing mechanisms, and continuous capacity building of the key stakeholders at national and county levels.